Second Five Year Plan (1956-61) Himachal Pradesh Administration - Planning Commission (Planning Commission, 1956)
Himachal Pradesh, as presently constituted, is comprised of erstwhile princely States previously known as the Punjab Hill States (except Nalagarh). These were consolidated into a single unit on the ,15th April, 1948 except Mandi which was merged with Himachal Pradesh from 1st May, 1948. The State of Bilaspur integrated into Himachal Pradesh on 1st July, 1954. The Pradesh has a land area of 10,904 square miles with a population of 11,09,466 according to the census of 1951. The average density of population per square mile is 102.
Himachal Pradesh Administration, Planning and Development Department